La terapia ocupacional y su incidencia en el aspecto psicomotor del adulto mayor del centro de atención Los Arupos durante el periodo mayo a julio 2013 Loja lineamientos alternativos - Godos Zapata, Jennifer Alexandra (2015)
The research was headed for the purpose of conducting a study of "OCCUPATIONAL THERAPY AND ITS IMPACT ON THE LOOK PSYCHOMOTOR ELDERLY CARE CENTER" THE ARUPOS "During the period May to July 2013 GUIDELINES ALTERNATIVE LOJA" the research is descriptive and explanatory, scientific, inductive, deductive methods were used; and as instruments Asalid Test (expert opinion) and a survey center staff. These methods and instruments were used to achieve the results of the problem; with a population of 23 older adults and 5 managers, sample was taken from a total of 12 people which corresponds to 7 adults and 5 older people working in the center. Once collected, organized and analyzed the information it was concluded that the main difficulties of seniors in fine motor skills are braided, buttoned, molded and punched as they are activities that require greater concentration and fine motor domain ; so what; the level of involvement of the elderly in occupational therapy is unsatisfactory, which means that there is an adequate participation when conducting therapies. Under the conclusions, we recommend: To the authorities, to encourage older adults to perform all the activities offered at the center in order to maintain the strengthening of the different areas included in the fine motor skills older adults, so the use of the proposal presented by the research called "The involvement in occupational therapy, a key to maintaining the fine motor skills of older base." is suggested. .